2018 International Energy Conversion Engineering Conference 2018
DOI: 10.2514/6.2018-4973
|View full text |Cite
|
Sign up to set email alerts
|

The Kilopower Reactor Using Stirling TechnologY (KRUSTY) Nuclear Ground Test Results and Lessons Learned

Abstract: The Kilopower nuclear ground testing nicknamed KRUSTY (Kilopower Reactor Using Stirling TechnologY) was completed at the Nevada Nuclear Security Site (NNSS) on March 21, 2018. This full scale nuclear demonstration verified the Kilopower reactor neutronics during startup, steady state, and transient operations in a space simulated environment. This was the first space reactor test completed for fission power systems in over 50 years and marked a turning point in NASA's nuclear program. The completed reactor pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Fission and fusion salt systems have two relatively unique challenges relative to other reactor coolants: (1) avoid freezing of the salt and (2) capture the tritium. Heat pipes have the potential to provide a simpler and lowercost solution to these challenges.…”
Section: Status Of Technology and Path Forwrdmentioning
confidence: 99%
“…Fission and fusion salt systems have two relatively unique challenges relative to other reactor coolants: (1) avoid freezing of the salt and (2) capture the tritium. Heat pipes have the potential to provide a simpler and lowercost solution to these challenges.…”
Section: Status Of Technology and Path Forwrdmentioning
confidence: 99%
“…Recent ground tests demonstrated a 1 kWe 'Kilopower' system is both simple and viable for future space missions. 2,3 Combining a fission power system, leveraged from the kilopower demonstration, with the NEXT ion propulsion system at 7 kWe enables orbiting very deep space objects including Kuiper Belt objects (KBOs). Given the ample power available when NEP is not operating it was found that both higher power active science instruments could be used as well as high data rate communications to return the data quickly (instead of months required by the power limited New Horizons S/C.…”
Section: Figure 1 Nep Kboo Spacecraft (S/c)mentioning
confidence: 99%
“…It was assumed that a Kilopower class reactor would be available for this mission. 2 Kilopower is a joint NASA/DOE project to investigate development of reactors (power levels 1-10 kWe) that can be integrated with a wide range of power conversion technologies. In 2018 the 1 kWe DC variant of the Kilopower design was successfully tested at a DOE site in Nevada.…”
Section: Power Assumptionsmentioning
confidence: 99%
“…Heat pipe is one of the most effective heat transfer device and It can transfer a large amount of heat through a small cross-section area over a long distance without any additional external power, which is widely used in the fields of Electronics [1], chemical industry [2][3], aerospace [4][5] and deep space exploration [6][7]. In recent years, many researchers have done a lot of research on the performance of heat pipe.…”
Section: Introductionmentioning
confidence: 99%